2001
DOI: 10.1002/poc.443
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism for oxime formation from methyl pyruvate

Abstract: Rate and equilibrium constants for methyl pyruvate oxime formation were determined as a function of pH over the range 0-7 in aqueous solution at 30°C and ionic strength 0.5 by spectrophotometric methods. The reaction occurs with rate-determining carbinolamine dehydration over the entire range of pH investigated. Carbinolamine dehydration is not susceptible to detectable general acid-base catalysis by a carboxylic acid buffer or hydroxylamine/hydroxylammonium ion buffer. Specific acid catalysis for carbinolamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…However, in the acid‐catalyzed model system, the rate‐determining step corresponds to the internal proton transfer step, Step 2. This observation, pH dependence of the rate of oxime/hydrazone formation, is in good agreement with the reported kinetic studies …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…However, in the acid‐catalyzed model system, the rate‐determining step corresponds to the internal proton transfer step, Step 2. This observation, pH dependence of the rate of oxime/hydrazone formation, is in good agreement with the reported kinetic studies …”
Section: Resultssupporting
confidence: 93%
“…Based on our calculations, Step 2 is the rate‐limiting step and requires a substantial activation energy. Kinetic studies for the formation of oximes under acidic conditions reported that the dehydration (decomposition) of carbinolamine was observed to be the rate‐limiting step in the pH range of 0 to 6 . The calculated value of activation barrier for this step, 31.36 kcal/mol, seems incompatible with the experimental observations now that oximes can be formed with and without catalyst from alkyl or aryl reactants within hours .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The kinetics of the oximation reaction has been studied in the past for various aldehydes and ketones . The reaction rate tends to vary widely among different carbonyl reagents because steric hindrance and electronic effects play an important role in the reactivity of carbonyl compounds . Another important factor is the reaction medium, as was observed while developing analytical methods for quantification of aldehydes and ketones in the 1960s…”
Section: Introductionmentioning
confidence: 99%